A conspectus of Mexican Melantiaceae including a description of new taxa of Schoenocaulon and Zigadenus - Frame, Dawn; Espejo, Adolfo; Lopez-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 1999)
Seven new taxa of Schoenocaulon and one more of Zigadenus from Mexico are herein described. In addition, a brief description of the Mexican genera of Melanthiaceae and a key to genera and species known from Mexico are given.